식물공장 시스템의 동향과 발전방향 - 김재훈(Jae Whune Kim) (Journal of plant biotechnology, 2010)
Plant factory is the fruit of the most advanced modern agricultural technology. This is a crop-producing technology that controls systematically sowing, cultivating, and harvesting crops within an indoor factory. Growing crops in a factory has advantages over traditional farming because it produces safer crops all year around due to clean environment and it is easier to hire workers at the factory. Developed countries has invested actively in this field for several decades because its economical and industrial impact are predicted to be enormous. Recently, Korea also begins to investigate this field actively to develop a system that may be competitive at global market, using technologies and human resources that Korea already has. The plant factory technology is currently less competitive than traditional farming because it requires a large initial investment and management cost and lacks cultivation technologies for various crops. However, I believe in solving these problems if plant biotechnologists participate in developing the plant factory system. If this technology is developed well in Korea, then it will play a great role in solving food and environmental issues. 식물공장 (plant factory)은 파종에서 재배 및 수확까지 실내에서 종합적으로 관리 제어되는 공장식 식물생산기술로 현대농업의 결정체이다. 식물공장은 청결한 환경에서 안전성 높은 농산물을 연중 생산할 수 있고, 작업환경이 좋아 노동력 확보가 수월하다. 선진국들은 수 십년 전부터 식물공장의 산업적 경제적 효과를 예측하고 이 분야에 많은 관심을 가지고 적극적으로 투자해 왔다. 최근 우리나라도 우수한 기술력과 인력을 적극 활용하여 국제 경쟁력이 있는 식물공장 시스템을 개발하고자 활발히 연구개발을 진행하고 있다. 식물공장은 초기투자비용의 과다, 전용 품종의 재배기술 부족, 운영비 절감 등의 문제점이 아직 해결되지 않아 기존 농업과 경쟁하기 어렵다. 그러나 식물생명공학 분야의 전문가들이 식물공장 시스템 개발에 적극 참여한다면 여러 문제점이 개선될 것이다. 환경변화에 의한 농작물 경작의 어려움에 당면하고 있는 농촌과 농업에 식물공장을 잘 활용한다면 농산물 경작의 문제점을 해결하고, 식량문제와 환경문제를 해결하는데 큰 역할을 할 수 있을 것이다.